Factors Influencing Work Performance Among Healthcare Personnel at Sultanah Bahiyah Hospital, Alor Setar - Noor Aziana, Iberahim (2009)
The main purpose of this study was to determine the relationships between job design and work performance among 240 randomly selected healthcare personnel in Sultanah Bahiyah Hospital, Kedah. The study also examined statistically significant differences in the respondents’ work performance when grouped by gender, age, marital status, tenure, number of years working in the current hospital, number of years working in other hospitals, and place of residence. In assessing job design, the Multimethod Job Design Questionnaire (Cronbach Alpha= 0.9064) developed by Campion (1988) was adopted, pilot-tested, and used in the research. In describing work performance, job evaluation records from the Human Resource Office in Sultanah Bahiyah Hospital were taken for the purpose of this study. Statistical analysis used were frequency counts, percentages, means, t-test, One-Way ANOVA, Post-Hoc Test, Pearson’s r, and Multiple Regression Analysis. Analyses were set at 0.05 level of significance using the SPSS (Version 12.0) computer software. Overall, the respondents “agreed” on the job design in the hospital. Across the sub-dimensions of job design, the respondents “agreed” on Motivational Approach, Biological Approach, and Perceptual-Motor Approach. However, respondents were “not sure” on Mechanistic Approach. The respondents experienced “high” level of work performance. There were statistically significant differences between work performance and (a) age, (b) marital status, (c) tenure, (d) number of years working in the current hospital, and (e) number of years working in other hospitals.